Application of Universal Time Coordinated if Rank-Synchronization System of Mobile Units - N. E. Lipakov (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The aim is to analyze principles of construction inter-aircraft navigation system with using in the rank-synchronization subsustem both of autonomous ant universal coordinated time. As result of-fered the improved work algorithm of rank-synchronization subsustem, providing interaction of user group under unstable connection with universal time coordinated source.